The Effect of Scientific Approach Toward Students’ Writing Achievement at Tenth Grade of SMA N 8 Jambi City - Morita Septi Rahayu; Khidayatul Munawwaroh; Nurul Fitri (JELT: Journal of English Language Teaching, 2020)
This research was done to find the effect of scientific approach toward students’ writing achievement at tenth grade of SMA N 8 Kota Jambi Academic Year 2019/2020. The researcher used a quantitative method and quasi-experimental design as the research methodology with simple random sampling. The purpose of this research is to find out whether there is any significant effect or not of scientific approach toward students’ writing achievement. The sample of this research was the tenth of science grade students at SMA N 8 Kota Jambi. The instrument of this research was tests. This study involved 56 students of the tenth grade students at SMA N 8 Kota Jambi academic year 2019/2020 as the object of the study and divided into two classes. Students’ writing achievement is effect after treatment using scientific approach learning method which is proven with students writing achievement higher than before treatment. The average pre-test control class 48,6 and post-test control class 78,8. Average pre-test experimental class 53,5 and post-test 90,5.  Using scientific approach in teaching writing descriptive text makes learning activity more effective and students can well understand learning material in treatment process. Thus the alternative hypothesis is accepted, the value of t-test higher than the value of t-table (3,93>2,004). Based on the finding above, it can be concluded that using scientific approach as learning method has significant effect of students writing achievement at tenth grade students of SMA N 8 Kota Jambi.Key Words: Effect, Writing Achievement, Scientific Approach.